2021
DOI: 10.48550/arxiv.2106.11109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New insight into the magnetism of degenerate stars from the analysis of a volume limited sample of white dwarfs

S. Bagnulo,
J. D. Landstreet

Abstract: Many stars evolve into magnetic white dwarfs, and observations may help to understand when the magnetic field appears at the stellar surface, if and how it evolves during the cooling phase, and, above all, what are the mechanisms that generate it. After obtaining new spectropolarimetric observations and combining them with previous literature data, we have checked almost the entire population of about 152 white dwarfs within 20 pc from the Sun for the presence of magnetic fields, with a sensitivity that ranges… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 147 publications
(493 reference statements)
0
2
0
Order By: Relevance
“…Our finding that the dynamo scenario can consistently explain the magnetic nature of NLTT 12758 (and the absence of clear signs of magnetism among close double white dwarfs otherwise) adds another piece of evidence to the already available support for the dynamo scenario for the generation of strong magnetic fields in white dwarfs: the dynamo is the only scenario that can explain the absence of strongly magnetic white dwarfs among young post common envelope binaries, it offers an explanation for the existence of the radio pulsing white dwarf binary AR Sco, it is consistent with the high occurrence rate of magnetic white dwarfs in cataclysmic variables (Schreiber et al 2021a), it naturally explains the absence of high accretion rate intermediate polars in globular clusters (Belloni et al 2021), and seems to be the reason behind the observed relation between magnetism and metal pollution (Schreiber et al 2021b). Considering that also single white dwarfs that are currently not metal polluted, might have accreted planetary material in the past and therefore gained angular momentum (Schreiber et al 2021b), the model might also explain the magnetism of old white dwarfs that currently do not show signs of accretion (Bagnulo & Landstreet 2021).…”
Section: Concluding Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our finding that the dynamo scenario can consistently explain the magnetic nature of NLTT 12758 (and the absence of clear signs of magnetism among close double white dwarfs otherwise) adds another piece of evidence to the already available support for the dynamo scenario for the generation of strong magnetic fields in white dwarfs: the dynamo is the only scenario that can explain the absence of strongly magnetic white dwarfs among young post common envelope binaries, it offers an explanation for the existence of the radio pulsing white dwarf binary AR Sco, it is consistent with the high occurrence rate of magnetic white dwarfs in cataclysmic variables (Schreiber et al 2021a), it naturally explains the absence of high accretion rate intermediate polars in globular clusters (Belloni et al 2021), and seems to be the reason behind the observed relation between magnetism and metal pollution (Schreiber et al 2021b). Considering that also single white dwarfs that are currently not metal polluted, might have accreted planetary material in the past and therefore gained angular momentum (Schreiber et al 2021b), the model might also explain the magnetism of old white dwarfs that currently do not show signs of accretion (Bagnulo & Landstreet 2021).…”
Section: Concluding Discussionmentioning
confidence: 94%
“…From an observational point of view, we need to expand the work of Bagnulo & Landstreet (2021) who presented the first volume limited (but still rather small) sample of white dwarfs and investigated how the incidence of magnetism depends on key parameters. As in SDSS-V white dwarfs are for the first time prime targets of an SDSS survey, we may indeed be able to analyze a large volume limited sample of white dwarfs in the near future.…”
Section: Concluding Discussionmentioning
confidence: 99%